A nickel-aluminum-based cermet composite resistant to molten aluminum corrosion, its preparation method and application
By introducing B2O3-TiB2 ceramic reinforced phase and Cu bonded phase into nickel-based alloys, NiAl-B2O3-TiB2-Cu composite materials are prepared, which solves the problems of creep resistance and brittleness of nickel-based alloys at high temperatures, and has achieved improvements in the corrosion resistance and mechanical properties of aluminum liquids, and is suitable for the cast aluminum alloy industry.
Patent Information
- Application Number
- CN202310826498.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2043-07-07
AI Technical Summary
The existing nickel-based alloy materials have high creep resistance and high brittleness at high temperatures, and the interface bonding strength between the enhanced phase and the nickel-based alloy is weak, making it difficult to have excellent corrosion resistance and mechanical properties of liquid aluminum at the same time.
NiAl intermetallic compound was used as the matrix, and B2O3-TiB2 ceramic reinforced phase and Cu were introduced as bonded phases. NiAl-B2O3-TiB2-Cu composite material was prepared by thermal explosion synthesis method. Combining Cu toughness and high temperature flowability of B2O3, it improved the material structure, reduced brittleness and increased density.
The prepared composite materials have excellent corrosion resistance of aluminum liquid and high temperature oxidation resistance, excellent mechanical properties, suitable for parts of the cast aluminum alloy industry, and the preparation process is simple and efficient.
Smart Images

Figure CN116970827B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials resistant to molten aluminum corrosion, and in particular to a nickel-aluminum-based molten aluminum corrosion-resistant composite material and a preparation method and application thereof. Background Art
[0002] With the advancement of industrial technology, aluminum alloys have gradually become an indispensable metal material in my country's industrial field due to their strong plasticity, high strength, and high production volume. However, due to the strong corrosiveness of molten aluminum, it can cause severe corrosion to metal parts that come into direct contact with the molten aluminum during the casting process, which has a significant impact on the development of the national economy. Therefore, there is an urgent need to develop new materials that are resistant to molten aluminum corrosion to meet the needs of aluminum industry production and application.
[0003] Single materials often struggle to overcome their inherent shortcomings. Metals have poor corrosion resistance to molten aluminum and are prone to failures such as pitting and thermal fatigue. While ceramics offer strong corrosion resistance to molten aluminum, they also suffer from brittle fracture and thermal shock resistance. Metal-ceramic composites can effectively mitigate the brittleness of single ceramic materials, improving overall strength and toughness, making them promising materials for resolving challenges in the aluminum alloy casting industry.
[0004] Currently, Zeng Yong of South China University of Technology has studied the preparation of Ti3AlC2 / TiAl3 composite materials and their resistance to molten aluminum corrosion and wear. Their resistance to molten aluminum corrosion and wear is 7 times higher than that of H13 steel. Chinese invention patent CN111440983A discloses a multi-scale boride-reinforced iron-based material resistant to high-temperature molten aluminum corrosion and its preparation method. This invention uses electric furnace smelting and casting to prepare a multi-scale boride-reinforced iron-based material with good molten aluminum corrosion resistance and toughness. Chinese invention patent CN103938050B discloses a high-density metal ceramic material resistant to molten aluminum corrosion. This invention uses hot-pressing assisted sintering of Ti powder, Ni powder, AlN and Al2O3 powder to prepare a high-density metal ceramic material resistant to molten aluminum corrosion.
[0005] Although the composite materials disclosed above have strong resistance to aluminum liquid corrosion, their thermal shock resistance and high-temperature oxidation resistance are still insufficient. At the same time, they are very prone to cracking under hot and cold alternating working conditions, which limits their use.
[0006] Nickel-based intermetallic compounds are widely used in equipment manufacturing materials in the chemical energy industry, nuclear energy industry, transportation and other fields due to their good corrosion resistance, high melting point, thermal stability, etc., such as engine turbine components, continuous casting machine rollers, extrusion dies, etc. However, they have low creep resistance, high brittleness, low high-temperature strength and creep resistance at high temperatures. Single NiAl is extremely limited as an industrial product.
[0007] At present, the high-temperature creep, mechanical strength and wear resistance of nickel-based alloys are mainly improved by ceramic phase reinforcement and surface modification methods. Reinforcement and wear-resistant phases represented by graphite and ceramic phases are added to the nickel-based alloy matrix, and nickel-based composite materials are formed through powder metallurgy process.
[0008] However, the bonding strength between the above-mentioned reinforcement phase and the nickel-based alloy interface is weak, and the distribution state of the reinforcement phase in the nickel-based alloy is difficult to control, making it difficult to obtain a NiAl-based metal-ceramic composite material with both excellent aluminum liquid corrosion resistance and mechanical properties. Summary of the Invention
[0009] Based on the above problems, the first purpose of the present invention is to provide a method for preparing a nickel-aluminum-based molten aluminum corrosion-resistant composite material with a simple and efficient preparation process that is easy to promote and apply. The nickel-aluminum-based molten aluminum corrosion-resistant composite material prepared by this method has good mechanical properties, excellent resistance to molten aluminum corrosion and high-temperature oxidation resistance.
[0010] The above-mentioned method for preparing the nickel-aluminum-based composite material resistant to aluminum liquid corrosion comprises the following steps:
[0011] Step 1: Weigh the raw materials
[0012] The raw materials are composed of the following components by mass percentage: a powder: 85-95wt%, TiB2 powder: 6-10wt%, B2O3 powder: 3-5wt%, Cu powder: 2-4wt%, wherein a powder is a mixture of Al powder and Ni powder in a molar ratio of 1:1;
[0013] Specifically, the purity of the Ni powder, Al powder, B2O3 powder, TiB2 powder and Cu powder in step 1 is greater than 98%.
[0014] Step 2: Ball milling
[0015] The raw materials were placed in a ball mill for ball milling, and after ball milling, the powder was sieved through a 200-mesh sieve to obtain NiAl-B2O3-TiB2-Cu powder, which was then dried;
[0016] Specifically, the ball milling material in step 2 is stainless steel balls, the ball-to-material ratio is 20:1, the ball milling time is 2-3 hours, and the ball milling speed is 100-200 r / min.
[0017] Step 3: Powder Compacting
[0018] The dried NiAl-B2O3-TiB2-Cu powder was placed in a homemade mold and pressed into a green body with a relative density of 80-95% on a press;
[0019] Specifically, the mixed powder is placed in a homemade mold and pressed into a blank on a press, and the pressure applied by the press is 200-300 MPa.
[0020] Specifically, the self-made mold is a graphite mold.
[0021] Step 4: Heat Explosion Synthesis
[0022] The green body is placed in a thermal explosion synthesis device, heated to 700-1100° C. in an Ar gas environment, and a pressure of 20-30 MPa is applied to the green body to perform a thermal explosion synthesis reaction to obtain a NiAl-B2O3-TiB2-Cu composite material.
[0023] Specifically, the pressed sample was placed in the reaction chamber of a thermal explosion synthesis device, which was first evacuated and then filled with Ar gas. The induction coil surrounding the thermal explosion synthesis device was heated to 700°C-1100°C. At the same time, a pressure of 20-30 MPa was applied by an upper pressure device to accelerate the discharge of gas until the reaction was completed. The sample was removed and air-cooled to room temperature to obtain a NiAl-B2O3-TiB2-Cu composite material.
[0024] The NiAl-B2O3-TiB2-Cu composite material prepared by the present invention uses a NiAl intermetallic compound as a matrix and Cu as a binder phase to synthesize a metal-ceramic composite material with ceramic materials TiB2 and B2O3. NiAl is highly favored due to its wide raw material availability, low cost, high high-temperature specific strength and specific stiffness, and good oxidation and corrosion resistance. However, as a single phase, it has the disadvantages of low creep resistance at high temperatures, high brittleness at room temperature, and low high-temperature strength and creep resistance. Therefore, the present invention synthesizes a B2O3-TiB2 ceramic reinforcement phase in situ to improve its mechanical properties, and adds a binder phase of Cu to increase the overall microstructure density, resulting in a composite material with excellent resistance to molten aluminum corrosion and mechanical properties.
[0025] TiB2 has a high melting point (about 2980℃), thermal shock resistance, high hardness, high elastic modulus (550Gpa) and good oxidation resistance at 1000℃, which can improve the thermal shock resistance and wear resistance of NiAl materials. It also has excellent properties such as strong resistance to aluminum liquid corrosion. However, TiB2 has poor high temperature toughness, low diffusion coefficient and poor sintering performance, which makes the sintering preparation of pure TiB2 material difficult. Therefore, metal Cu can be used as a bonding phase. Its excellent toughness and low melting point can improve the shortcomings of TiB2 such as poor toughness and difficulty in sintering. At the same time, TiB2 is different from most The wettability of several metals is poor, so it is necessary to select Cu, a metal with good wettability with TiB2, as the bonding phase; B2O3 can improve the high-temperature fluidity and spreadability of NiAl composite materials, making them form denser materials during the casting process. Secondly, it can also reduce the wettability of NiAl to molten aluminum liquid, increase the contact angle, delay or prevent more serious oxidation of the coating, and generate borides, which have an inhibitory effect on the peeling and dissolution of corrosion products; in addition, Cu as a bonding phase not only improves the density of the TiB2 coating, improves the crack tendency, makes the material structure more uniform, and reduces the brittleness of the material.
[0026] The present invention also relates to a nickel-aluminum-based composite material resistant to aluminum liquid corrosion obtained by the above preparation method.
[0027] Another object of the present invention is to provide a nickel-aluminum-based metal ceramic coating resistant to molten aluminum corrosion, wherein the metal ceramic coating is prepared by a spraying process from a nickel-aluminum-based metal ceramic composite material resistant to molten aluminum corrosion.
[0028] The beneficial effects of the present invention are:
[0029] (1) The nickel-aluminum-based aluminum-liquid corrosion-resistant metal-ceramic composite material prepared by the present invention has a NiAl intermetallic compound as a matrix, and introduces B2O3-TiB2 as a ceramic reinforcement phase through in-situ synthesis in the NiAl matrix, and Cu as a bonding phase, so that the material structure is more uniform and the brittleness of the material is reduced. The obtained NiAl-B2O3-TiB2-Cu composite material has good mechanical properties and high-temperature oxidation resistance;
[0030] (2) The nickel-aluminum-based aluminum liquid corrosion-resistant metal ceramic composite material prepared by the present invention can reduce the wettability of molten aluminum liquid, increase the contact angle, delay or prevent more serious oxidation of the coating, and secondly, can generate boride, which has an inhibitory effect on the peeling and dissolution of corrosion products, thereby improving the aluminum liquid corrosion resistance;
[0031] (3) The preparation process of the composite material is simple and efficient, easy to promote and apply, and can be widely used in parts of the aluminum alloy casting industry. It has high application value. The metal-ceramic composite material prepared by this method has high density, good mechanical properties, and strong resistance to aluminum liquid corrosion;
[0032] (4) The present invention adopts a thermal explosion synthesis device for preparation. Thermal explosion synthesis has less heat loss during the reaction process, which can keep the synthetic product in the liquid phase for a longer time during the reaction process, thereby achieving grain refinement of the material, reducing internal defects of the prepared material, and improving the density of the material; the induction coil is used for heating, which has high heating efficiency and is convenient for introducing protective gas, thereby improving the preparation efficiency; the upper pressure device is used to assist in pressurization to facilitate the removal of air in the product in the liquid phase, reduce the generation of pores, and obtain a relatively dense synthetic product; BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 The micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1;
[0035] Figure 2 The XRD pattern of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1;
[0036] Figure 3 Schematic diagram of the thermal explosion synthesis device in Examples 1-3 of the present invention;
[0037] Figure 4 The micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for different times, wherein Figure 4 a-4c are SEM micromorphology images after corrosion for 8h, 24h, and 36h, respectively;
[0038] Figure 5 a is a micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for 12 hours; Figure 5 b is the SEM micromorphology of H13 steel after corrosion for 12 h;
[0039] Figure 6a is a wettability test characterization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1;
[0040] Figure 6 b is the wettability test characterization diagram of the Al-TiB2-Cu composite material prepared in the control group;
[0041] Figure 7 The corrosion depth of the three examples and the control group changes with time; DETAILED DESCRIPTION
[0042] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention are within the scope of protection of the present invention.
[0043] Example 1
[0044] Step 1: Weigh the raw materials
[0045] Al powder and Ni powder are mixed in a molar ratio of 1:1 to obtain powder a, and 88 wt% of powder a, 6 wt% of TiB2 powder, 4 wt% of B2O3 powder, and 2 wt% of Cu powder are weighed and mixed to form a raw material;
[0046] Step 2: Ball milling
[0047] The raw materials were placed in a ball mill for ball milling. The ball milling material was stainless steel balls with a ball-to-material ratio of 20:1. Dry ball milling was performed at a ball milling speed of 100 r / min and a ball milling time of 3 h. After ball milling, the powder was sieved through a 200-mesh sieve to obtain NiAl-B2O3-TiB2-Cu powder, which was then placed in a vacuum drying oven for drying at a temperature of 70°C and a vacuum degree of -0.1 MPa for 12 h.
[0048] Step 3: Powder Compacting
[0049] The dried NiAl-B2O3-TiB2-Cu powder was placed in a homemade graphite mold and pressed on a press with a pressure of 300 MPa to produce a green body with a relative density of 95%.
[0050] Step 4: Heat Explosion Synthesis
[0051] The green body was placed in a reaction chamber in a thermal explosion synthesis device. In an Ar gas environment, the induction coil surrounding the reaction chamber was heated to 700°C to carry out a thermal explosion synthesis reaction. At the same time, a pressure of 25 MPa was applied to the green body to accelerate gas discharge and reduce the generation of pores. After the reaction was completed, the green body was air-cooled to room temperature to obtain a NiAl-B2O3-TiB2-Cu composite material.
[0052] The present invention uses XL-30FEG scanning electron microscope (SEM) to analyze the physical phase and observe the morphology of the corrosion layer. Figure 1 , Figure 1 This is the micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1. Figure 2 This is the XRD pattern of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1.
[0053] Example 2
[0054] Step 1: Weigh the raw materials
[0055] Al powder and Ni powder are mixed in a molar ratio of 1:1 to obtain powder a, and 91 wt% of powder a, 8 wt% of TiB2 powder, 5 wt% of B2O3 powder, and 4 wt% of Cu powder are weighed and mixed to form a raw material;
[0056] Step 2: Ball milling
[0057] The raw materials were placed in a ball mill for ball milling. The ball milling material was stainless steel balls with a ball-to-material ratio of 20:1. Dry ball milling was performed at a ball milling speed of 200 r / min and a ball milling time of 2.5 h. After ball milling, the powder was passed through a 200-mesh sieve to obtain NiAl-B2O3-TiB2-Cu powder, which was then placed in a vacuum drying oven for drying at a temperature of 70°C and a vacuum degree of -0.1 MPa for 12 h.
[0058] Step 3: Powder Compacting
[0059] The dried NiAl-B2O3-TiB2-Cu powder was placed in a homemade graphite mold and pressed on a press with a pressure of 250 MPa to produce a green body with a relative density of 85%.
[0060] Step 4: Heat Explosion Synthesis
[0061] The green body was placed in a reaction chamber in a thermal explosion synthesis device. In an Ar gas environment, the induction coil surrounding the reaction chamber was heated to 900°C to carry out a thermal explosion synthesis reaction. At the same time, a pressure of 30 MPa was applied to the green body to accelerate the discharge of gas and reduce the generation of pores. After the reaction was completed, the green body was air-cooled to room temperature to obtain a NiAl-B2O3-TiB2-Cu composite material.
[0062] Example 3
[0063] Step 1: Weigh the raw materials
[0064] Al powder and Ni powder are mixed in a molar ratio of 1:1 to obtain powder a, and 93 wt% of powder a, 10 wt% of TiB2 powder, 5 wt% of B2O3 powder, and 3.5 wt% of Cu powder are weighed and mixed to form a raw material;
[0065] Step 2: Ball milling
[0066] The raw materials were placed in a ball mill for ball milling. The ball milling material was stainless steel balls with a ball-to-material ratio of 20:1. Dry ball milling was performed at a ball milling speed of 150 r / min and a ball milling time of 2 h. After ball milling, the powder was passed through a 200-mesh sieve to obtain NiAl-B2O3-TiB2-Cu powder, which was then placed in a vacuum drying oven for drying at a temperature of 70°C and a vacuum degree of -0.1 MPa for 12 h.
[0067] Step 3: Powder Compacting
[0068] The dried NiAl-B2O3-TiB2-Cu powder was placed in a homemade graphite mold and pressed on a press with a pressure of 250 MPa to produce a green body with a relative density of 88%.
[0069] Step 4: Heat Explosion Synthesis
[0070] The green body is placed in a reaction chamber in a thermal explosion synthesis device. In an Ar gas environment, the induction coil surrounding the reaction chamber is heated to 1000°C to carry out the thermal explosion synthesis reaction. At the same time, a pressure of 30MPa is applied to the green body to accelerate the exhaust of gas and reduce the generation of pores. After the reaction is completed, the green body is air-cooled to room temperature to obtain a NiAl-B2O3-TiB2-Cu composite material. Figure 3 , Figure 3 for Figure 3 Schematic diagram of the thermal explosion synthesis device in Examples 1-3 of the present invention.
[0071] Mechanical properties testing
[0072] In the present invention, the Archimedes drainage method is used to test the density of the NiAl-B2O3-TiB2-Cu composite material; the hardness of the NiAl-B2O3-TiB2-Cu composite material is measured using an HRS-150 Rockwell hardness tester; with reference to the national standard GB / T6569-2006, the three-point bending test method is used to test the flexural strength of the NiAl-B2O3-TiB2-Cu composite material, and the fracture toughness test is carried out according to the GB 7732 standard. The mechanical properties of the NiAl-B2O3-TiB2-Cu composite materials obtained in Examples 1-3 are respectively tested using the above methods, and the test results are shown in the table below.
[0073] density hardness Bending strength fracture toughness Example 1 91.7% 82.6HRA 1862.1MPa <![CDATA[26.9MPa·m 1 / 2 ]]> Example 2 84.5% 79.1HRA 1756.8MPa <![CDATA[25.7MPa·m 1 / 2 ]]> Example 3 87.2% 81.7HRA 1728.6MPa <![CDATA[26.4MPa·m 1 / 2 ]]>
[0074] From the above data, it can be seen that the main mechanical properties of the NiAl-B2O3-TiB2-Cu composite material prepared by the present invention are excellent (the highest density is not less than 91.7%, the highest flexural strength is not less than 1728MPa, and the highest fracture toughness is not less than 25.7MPa·m 1 / 2 , the maximum hardness is not less than 79.1HRA). Compared with the existing conventional preparation process, the number of pores in the NiAl-B2O3-TiB2-Cu composite material prepared by the preparation process of the present invention is reduced, indicating that the density is further improved and the material structure is more uniform. At the same time, the number of transgranular fractures is increased, which will consume more energy when bearing, improve its bending strength, and improve the comprehensive mechanical properties.
[0075] Liquid aluminum corrosion resistance test
[0076] The NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 (hereinafter referred to as the sample) was cut using a cutting machine, preferably at the center of the sample, into several small rectangular samples measuring 4×5×10 mm. The surface of the small sample was polished with sandpaper to remove the oxide film on the surface of the small sample. The sample was then cleaned with acetone in an ultrasonic cleaner and finally dried in a vacuum drying oven to obtain the treated small sample.
[0077] Then, a micrometer was used to measure the thickness of the small sample before corrosion. The small sample was then placed in a graphite crucible filled with 700°C aluminum liquid and a corrosion test was carried out on the test sample using pure aluminum melt. After the aluminum ingot was melted, it was kept warm in a resistance furnace and corroded for 8h, 12h, 24h, and 36h, respectively. After being taken out, the residual aluminum solution on the surface was cleaned with NaOH solution, then rinsed with ionized water, and finally cleaned in ethanol with ultrasound.
[0078] In addition, H13 steel control test group was added
[0079] The present invention adopts XL-30FEG scanning electron microscope (SEM) to analyze the physical phase and observe the morphology of the corrosion layer, and uses X-ray diffractometer (XRD) to analyze the surface phase structure thereof.
[0080] Nano Measure software was used in conjunction with SEM images of corrosion cross-sections to measure the average thickness of the corrosion layer. The corrosion rate was then calculated to measure the corrosion effect. The calculation formula is v = (H1-H2) / 2t, where H1 is the thickness of the sample before the corrosion test, H2 is the thickness of the sample after the corrosion test, and t is the corrosion time. Before the corrosion test, the pre-corrosion thickness (H1) was accurately measured with a micrometer. The cross-section of the sample after corrosion was then observed under a scanning electron microscope. The remaining thickness (H2) of the sample after corrosion was measured using the software.
[0081] The corrosion depth and corrosion rate of the samples at different times were calculated according to the above calculation formula. The average corrosion rate of the NiAl-B2O3-TiB2-Cu composite material obtained in Example 1 was 3.1×10 -3 mm / h, while the average corrosion rate of H13 steel is 8.2×10 -3 mm / h.
[0082] Figure 4 a is the micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for 8 hours, Figure 4 b is the micromorphology SEM organization picture of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for 24 hours; Figure 4 c is the SEM micromorphology of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for 36 hours.
[0083] It can be seen from the figure that there is a gap between the aluminum liquid and the composite material in the early stage of corrosion, and the wettability of the aluminum liquid and the material is very poor. As the corrosion time increases, the aluminum liquid and the base material become wetted and the two are tightly bonded.
[0084] See also Figure 5 ,in Figure 5 a is the micromorphology SEM organization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 after corrosion for 12 hours, Figure 5 b is the SEM micromorphology of H13 steel after corrosion for 12 h;
[0085] from Figure 5From top to bottom in a, there are aluminum layer, corrosion layer, and substrate. From the picture after 12 hours of corrosion, it can be found that the aluminum liquid has slightly corroded the composite material, but the corrosion layer has not separated from the composite material and is free in the aluminum liquid. It also hinders the aluminum liquid from further corroding the substrate, thereby reducing the corrosion rate, and the material still maintains its original shape. Figure 5 As can be seen in Figure b, the corrosion of H13 steel by molten aluminum is very obvious, and the corrosion layer has separated from the H13 steel, and H13 has shown slight cracks and holes. This shows that the metal ceramic material obtained in Example 1 has greatly improved its resistance to molten aluminum corrosion.
[0086] Test on improving overall wettability of composite materials by B2O3
[0087] In order to prove that B2O3 can improve the overall wettability of the material, a control group was designed with whether the raw materials of the composite material contained B2O3 powder as the variable to conduct wettability experiments.
[0088] The wettability test was performed on the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1 and the Al-TiB2-Cu composite material of the control group. The preparation method and parameters of the Al-TiB2-Cu composite material of the control group were the same as those of Example 1, the main difference being that the raw material components did not contain B2O3.
[0089] The specific steps for wettability test of NiAl-B2O3-TiB2-Cu composite material are as follows:
[0090] The high-temperature vacuum wetting furnace includes a furnace body, a vacuum system, a heating system, a dripping system, a camera system and a data processing system; a lifting platform is provided in the furnace body, and a pure Al storage pipe is provided above the lifting platform.
[0091] The process of the sessile drop method is as follows: first, pure Al is placed on the lifting platform as a sample platform, and then the prepared NiAl-B2O3-TiB2-Cu composite material is placed horizontally on the sample platform, and the substrate is adjusted to a horizontal state by a leveling ball; 3The metal particles are stored in the pure Al storage tube to prevent the metal particles from sliding into the furnace during the heating process; the furnace door is closed, the temperature control cabinet is adjusted to heat the furnace at a rate of 20°C / min according to the program, high-purity argon is filled into the furnace, and then the temperature is continued to be raised to 850°C. After the temperature is kept stable for 3 to 7 minutes, the metal particles in the pure Al storage tube are dropped onto the 850°C NiAl-B2O3-TiB2-Cu composite material. The Al metal quickly melts and wets and spreads on the NiAl-B2O3-TiB2-Cu composite material substrate. At this time, a digital camera starts to take pictures, and the pictures taken are transferred to a computer to take pictures of the Al droplets, thereby recording the shape changes of the Al droplets in contact with the NiAl-B2O3-TiB2-Cu composite material. Then, data processing and analysis are performed, and finally, after the furnace chamber is cooled, the sample is taken out.
[0092] Among them, data processing software includes ADSA (Axisymmeteric drop shape analysis), SESDROPD and FTA32.
[0093] When the wettability test of the control group Al-TiB2-Cu composite material was carried out, the steps were the same as above.
[0094] See also Figure 6 ,in Figure 6 a is a wettability test characterization diagram of the NiAl-B2O3-TiB2-Cu composite material prepared in Example 1, Figure 6 b is a characterization diagram of the wettability test of the Al-TiB2-Cu composite material prepared in the control group; from the comparison in the figure, it can be seen that the metal-ceramic composite material containing B2O3 components (i.e., NiAl-B2O3-TiB2-Cu composite material) has a larger contact angle than the metal-ceramic composite material not containing B2O3 components (i.e., NiAl-TiB2-Cu composite material), which reduces the wettability to molten aluminum liquid, hinders the peeling and dissolution of corrosion products, and thus improves the corrosion resistance to aluminum liquid.
[0095] Application Examples
[0096] The NiAl-B2O3-TiB2-Cu metal ceramic composite material prepared in Example 1 is sprayed onto a substrate using an active combustion high velocity gas spraying process to obtain a metal ceramic coating, wherein the substrate may be 316L stainless steel.
[0097] The activated combustion high-velocity gas spraying process is a supersonic flame spraying technology. Its characteristic is that the high-speed airflow generated by the combustion of compressed air and fuel heats the powder without completely melting it. At the same time, the powder is accelerated to more than 700m / s and impacts the substrate, forming a coating with extremely low oxide content and extremely high density, thereby improving the corrosion resistance of metals or alloys such as stainless steel to molten aluminum.
[0098] The above are merely examples of the present application and are not intended to limit the scope of protection of the present application. Those skilled in the art will appreciate that various modifications and variations are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present application shall be included within the scope of protection of the present application.
Claims
1. A method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion, characterized in that: The following steps are involved: Step 1: Weigh the raw materials The raw materials are composed of the following components by mass percentage: a powder: 85-95wt%, TiB2 powder: 6-10wt%, B2O3 powder: 3-5wt%, Cu powder: 2-4wt%, wherein a powder is a mixture of Al powder and Ni powder in a molar ratio of 1:1; Step 2: Ball milling The raw materials were placed in a ball mill for ball milling, and after ball milling, the powder was sieved through a 200-mesh sieve to obtain NiAl-B2O3-TiB2-Cu powder, which was then dried; Step 3: Powder Compacting The dried NiAl-B2O3-TiB2-Cu powder was placed in a homemade mold and pressed into a green body with a relative density of 80-95% on a press; Step 4: Heat Explosion Synthesis The green body is placed in a thermal explosion synthesis device, heated to 700-1100° C. in an Ar gas environment, and a pressure of 20-30 MPa is applied to the green body to perform a thermal explosion synthesis reaction to obtain a NiAl-B2O3-TiB2-Cu composite material.
2. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: The purity of the Ni powder, Al powder, B2O3 powder, TiB2 powder and Cu powder in step 1 is greater than 98%.
3. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: In step 1, the particle sizes of Ni powder and Al powder are less than 30 μm, and the particle sizes of B2O3 powder, TiB2 powder and Cu powder are all less than 50 μm.
4. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: The ball milling material in step 2 is stainless steel balls, the ball-to-material ratio is 20:1, the ball milling time is 2-3 hours, and the ball milling speed is 100-200 r / min.
5. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: The pressure applied by the press in step 3 is 200-300 MPa.
6. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: The specific process of thermal explosion synthesis in step 4 includes: The pressed sample was placed in a reaction chamber of a thermal explosion synthesis device, which was first evacuated and then filled with Ar gas. The induction coil surrounding the thermal explosion synthesis device was heated to 700°C-1100°C. At the same time, a pressure of 20-30 MPa was applied by an upper pressure device to accelerate the exhaust of gas until the reaction was completed. The sample was removed and air-cooled to room temperature to obtain a NiAl-B2O3-TiB2-Cu composite material.
7. The method for preparing a nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion according to claim 1, characterized in that: The homemade mold described in step 3 is a graphite mold.
8. A nickel-aluminum-based metal-ceramic composite material resistant to aluminum liquid corrosion prepared by the preparation method according to any one of claims 1 to 7.
9. A nickel-aluminum-based metal ceramic coating resistant to aluminum liquid corrosion, characterized in that: The metal ceramic coating is prepared by spraying the nickel-aluminum-based aluminum liquid corrosion-resistant metal ceramic composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Anti-aluminum corrosion high-density cermet material
CN103938050B
Multi-scale boride reinforced high-temperature-resistant molten aluminum erosion-resistant iron-based material and preparation method thereof
CN111440983A
Preparation method of NiAl / WC composite with high-temperature wear resistance
CN107142397A
Method of manufacturing ingots for use in making objects having high heat, thermal shock, corrosion and wear resistance
US5380482A